Making Humanitarian Crises Emotions and Images in History - Edgar, Brenda Lynn; Gorin, Valérie; Martín-Moruno, Dolores (Palgrave Studies in the History of Emotions, 2022)
'Wide-ranging but tightly focused, this brilliant volume shows us the innovative analytical possibilities afforded by a sophisticated approach that critically blends the history of emotions, the history of the senses and the history of experience with new ways of handling visual and material sources.' - Rob Boddice, Tampere University, Finland This open access collection of essays explores the emotional agency of images in the construction of 'humanitarian crises' from the nineteenth century to the present. Using the prism of the histories of emotions and the senses, the chapters examine the pivotal role images have in shaping cultural, social and political reactions to the suffering of others and to the establishment of the international networks of solidarity. Questioning certain emotions assumed to underlie humanitarianism such as sympathy, empathy and compassion, they demonstrate how the experience of such emotions has shifted over time. Understanding images as emotional objects, contributors from a wide horizon of disciplines explore how their production, circulation and reception has been crucial to the perception of humanitarian crises in a long-term historical perspective. Brenda Lynn Edgar is Senior Teaching and Research Associate at the Institute for Ethics, History and Humanities at theUniversity of Geneva, Switzerland. Her research focuses on the material culture history of photography. She has published on decorative photographic practices, landscape photography used in clinical environments, and women humanitarians in anthropological cinema. Valérie Gorin is Senior Lecturer and Researcher at the Geneva Center of Humanitarian Studies, a joint center of the University of Geneva and the Graduate Institute, Switzerland. A historian and media scholar, she has published extensively on humanitarian history, visual culture and digital communication since a decade. Dolores Martín-Moruno is Swiss National Science Foundation Professor at the Institute for Ethics, History and the Humanities at the Faculty of Medicine of the University of Geneva, Switzerland. She has published widely on the history of emotions and the history of humanitarian relief.